Reguła Pierwotna Zakonu Ubogich Rycerzy Chrystusa i Świątyni Salomona = The Latin Rule of the Poor Knights of Christ and the Temple of Solomon - Wasilkiewicz, Kamil (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The Latin Rule of the Knights of the Temple of Solomon was created between 1119 and 1128. It was written, edited and approved during the synod in Troyes in January 1128 and included 72 articles referring to the most important issues for the Knights Templars.
Keywords: Zakon Ubogich Rycerzy Chrystusa i Świątyni Salomona